Gambaran Stres Keluarga dalam Merawat Anggota Keluarga yang Menjalani Kemoterapi di Rumah Sakit Tingkat III Baladhika Husada Jember - Harianto, Dwi; Murtaqib, Murtaqib; Kushariyadi, Kushariyadi (Jurnal Ilmiah Ners Indonesia, 2021)
The family role changes occur in families who care for chemotherapy patients can cause an increasing stress levels in the family. It has a major influence on improving the health of patients who are undergoing chemotherapy, because the family's ability to provide care to patients cannot be given optimally. The study aims to analyze how the description of family stress in caring for family members undergoing chemotherapy at Baladika Husada Level III Hospital Jember. The study uses a quantitative descriptive design, the sample of this study was collected by purposive sampling technique involving as many as 192 families. The respondents in this study are nuclear or main families who treat patients undergoing chemotherapy. The average age of respondents in this study was 42.40 years old. The data collected using the DASS 42 questionnaire to measure the level of stress that occurs in families. . The data analysis was carried out by observing the frequency table. The results of the study stated that 50.5% of families experience severe stress, 23.4% of families experience moderate stress, 16.1% of families experience very severe stress, 9.4% of families experience mild stress and 0.5% of families are under normal stress . The conclusions obtained from the results of the study show that families who care for patients undergoing chemotherapy experience severe stress. The results of this study are expected to be one of the reference to nurses  for not only focus on patients, but also provide counseling to families who care for patients undergoing chemotherapy.